2019
DOI: 10.1007/s41030-019-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Effect of Breathing Pattern on Aerosol Delivery During High-Flow Nasal Therapy

Abstract: Introduction: The use of concurrent aerosol delivery during high-flow nasal therapy (HFNT) may be exploited to facilitate delivery of a variety of prescribed medications for inhalation. The study assessed the effect of tidal volume, breath rate, and inspiratory:expiratory (I:E) ratio on the quantity of aerosol captured at the level of the trachea during simulated HFNT. Methods: Testing was completed according to a factorial statistical design of experiments (DOE) approach. Tracheal dose was characterized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
4
29
0
2
Order By: Relevance
“…With unit dose administration, the inhaled dose was 10% to 15% in similar pediatric models, which was consistent with our findings using unit dose delivery. Interestingly, at low administered gas flow setting (4‐5 L/min), inhaled dose in Ari's recent study that used albuterol with concentration of 2.5 mg/3 mL was only 3.27% ± 0.4%, in contrast to 13.84% ± 0.42% in Bennett et al's study, which utilized a higher concentration (2 mg/mL) with similar anatomical models and gas flow settings. Besides the slight difference between the tidal volumes (100 vs 150 mL), the low vs high concentrations in two studies may partially contribute to the different inhaled doses, which supports our finding that high‐concentrated albuterol had higher delivery efficiency than low concentration.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…With unit dose administration, the inhaled dose was 10% to 15% in similar pediatric models, which was consistent with our findings using unit dose delivery. Interestingly, at low administered gas flow setting (4‐5 L/min), inhaled dose in Ari's recent study that used albuterol with concentration of 2.5 mg/3 mL was only 3.27% ± 0.4%, in contrast to 13.84% ± 0.42% in Bennett et al's study, which utilized a higher concentration (2 mg/mL) with similar anatomical models and gas flow settings. Besides the slight difference between the tidal volumes (100 vs 150 mL), the low vs high concentrations in two studies may partially contribute to the different inhaled doses, which supports our finding that high‐concentrated albuterol had higher delivery efficiency than low concentration.…”
Section: Discussionsupporting
confidence: 91%
“…Previous in vitro and in vivo studies on aerosol delivery via HFNC all utilized unit dose with a single concentration . With unit dose administration, the inhaled dose was 10% to 15% in similar pediatric models, which was consistent with our findings using unit dose delivery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Several factors influence aerosol drug delivery to the lungs, including the aerosol-generating device, the size distribution of the inhaled aerosol, the gas-flow rate, the inhalation pattern and the type of interface [5][6][7][8][9].Dysart et al [10] reported that the use of high-flow nasal therapy (HFNT) devices is rapidly growing in the clinical setting, for different age groups with a range of disease conditions. High-flow nasal therapy studies have reported gas-flow rates of 3 to 20 L/min for paediatrics, and 5 to 60 L/min for adults [11][12][13][14]. Studies have reported that several factors influence the quantity of aerosol available for inhalation, including the rate of gas flow delivered, the size of the nasal prongs, humidification, the size of the aerosol droplets and the aerosol generator type and position [11,13,15].…”
mentioning
confidence: 99%